2011
DOI: 10.1016/j.molcel.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP/PKA Pathway Rapidly Activates SIRT1 to Promote Fatty Acid Oxidation Independently of Changes in NAD+

Abstract: The NAD+-dependent deacetylase SIRT1 is an evolutionarily conserved metabolic sensor of the Sirtuin family that mediates homeostatic responses to certain physiological stresses such as nutrient restriction. Previous reports have implicated fluctuations in intracellular NAD+ concentrations as the principal regulator of SIRT1 activity. However, here we have identified a cAMP-induced phosphorylation of a highly conserved serine (S434) located in the SIRT1 catalytic domain that rapidly enhanced intrinsic deacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
266
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(285 citation statements)
references
References 44 publications
16
266
3
Order By: Relevance
“…In ter est ingly, SOX2 di rectly up reg u lates the tran scrip tion of sev eral genes re lated to glu t a mine and lipid me tab o lism, but their rel e vance for the stem like prop er ties of tu mor cells re mains un known [243]. An other pro tein in volved in en ergy me tab o lism reg u la tion and EMT is the cAMP ac ti vated ki nase PKA (pro tein ki nase A), which reg u lates di verse meta bolic path ways, rang ing from gly col y sis to lipid ox i da tion [244,245]. Pre vi ously it has been shown to be ac ti vated by in ter mit tent hy poxia [246], while it has been re cently shown that its ac ti va tion in hibits the mes enchy mal phe no type by in duc ing tran si tion to ep ithe lial state and in hibit ing CICs [247].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In ter est ingly, SOX2 di rectly up reg u lates the tran scrip tion of sev eral genes re lated to glu t a mine and lipid me tab o lism, but their rel e vance for the stem like prop er ties of tu mor cells re mains un known [243]. An other pro tein in volved in en ergy me tab o lism reg u la tion and EMT is the cAMP ac ti vated ki nase PKA (pro tein ki nase A), which reg u lates di verse meta bolic path ways, rang ing from gly col y sis to lipid ox i da tion [244,245]. Pre vi ously it has been shown to be ac ti vated by in ter mit tent hy poxia [246], while it has been re cently shown that its ac ti va tion in hibits the mes enchy mal phe no type by in duc ing tran si tion to ep ithe lial state and in hibit ing CICs [247].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The inhibition of muscle PDE4 at least partially accounts for the beneficial effects of resveratrol on metabolism, including improved glucose tolerance, by activation of cAMP/Epac/Sirt1 pathway (Park et al 2012). Whether PKA is involved in this process remains unknown, but it should be noted that PKA can directly phosphorylate and activate SIRT1 in skeletal muscles (Gerhart-Hines et al 2011). Consistently, PDE content in skeletal muscle is positively related to fasting plasma glucose level in diabetic patients (Szendroedi et al 2011), suggesting a correlation between suppressed cAMP signaling and impaired glucose homeostasis.…”
Section: Camp/pka In Skeletal Musclementioning
confidence: 99%
“…Pharmacological or physiological stimulation of β-adrenergic signaling in skeletal muscle leads to PKA-dependent activation of SIRT1 which promotes fatty acid oxidation and energy expenditure (Gerhart-Hines et al 2011). The monounsaturated fatty acid oleic acid is able to improve skeletal muscle insulin resistance partially through a PKAdependent mechanism (Coll et al 2008).…”
Section: Camp/pka In Skeletal Musclementioning
confidence: 99%
“…The principal transcriptional effector of this pathway is the CREB transcription factor, whose phosphorylation by PKA promotes CREB activity and target gene transcription (Mayr and Montminy 2001). PKA activation can also enhance the expression of PGC-1a, through the intermediacy of CREB (Herzig et al 2001), as well as directly activate the catalytic function of SIRT1 (Gerhart-Hines et al 2011). Biologically, one of the most salient examples of the power of cAMP-mediated effects on mitochondrial function is found in the adaptive nonshivering thermogenic response to lower temperatures (Cannon and Nedergaard 2004).…”
Section: Calcium Signalingmentioning
confidence: 99%